PFSENSE: teletrabalho durante a Pandemia do Covid-19 - BARROSO, Raianderson de Oliveira (Instituto Federal do Amapá, 2021)
Considering that the tool has a large number of applications and that these offer several benefits to users in general, research is being carried out on Pfsense as a solution for teleworking during the Covid-19 pandemic. Therefore, it is necessary to address the main features and advantages, the implementation of an analogous network, configuration of remote services and applications used in companies. Then, a bibliographical research is carried out, based on digital materials, academic researches and books on the subject, and an explanatory research, in order to explain concepts related to the studied subject. Therefore, it appears that the software enables the network administrator to manage an infrastructure with mechanisms for easy configuration and maintenance and the use of remote access solutions to assist in the continuation and productivity of the company, which imposes the verification that the services offered by the Pfsense server fulfills the role of maintaining connectivity and fluidity in the communication of users of organizations during the covid-19 pandemic.